Malachite Green Assay for the Discovery of Heat-Shock Protein 90 Inhibitors - Gupta, Sayan Dutta; Song, Dae-Geun; Lee, SueJung; Lee, Jae Wook; Park, Jin-Soo; Prodromou, Chrisostomos; Pan, Cheol-Ho (MYJoVE Corporation, 2023)
Heat shock protein 90 (Hsp90) is a promising anticancer target because of its chaperoning effect on multiple oncogenic proteins. The activity of Hsp90 is dependent on its ability to hydrolyze adenosine triphosphate (ATP) to adenosine diphosphate (ADP) and free phosphate. The ATPase activity of Hsp90 is linked to its chaperoning function; ATP binds to the N-terminal domain of the Hsp90, and disrupting its binding was found to be the most successful strategy in suppressing Hsp90 function. The ATPase activity can be measured by a colorimetric malachite green assay, which determines the amount of free phosphate formed by ATP hydrolysis. Here, a procedure for determining the ATPase activity of yeast Hsp90 by using the malachite green phosphate assay kit is described. Further, detailed instructions for the discovery of Hsp90 inhibitors by taking geldanamycin as an authentic inhibitor is provided. Finally, the application of this assay protocol through the high-throughput screening (HTS) of inhibitor molecules against yeast Hsp90 is discussed.